2023
DOI: 10.3389/fpsyg.2022.1066358
|View full text |Cite
|
Sign up to set email alerts
|

The importance of prevention programs to reduce bullying: A comparative study

Abstract: Bullying is a growing and increasingly worrying phenomenon. In recent years, a number of different bullying prevention programs have been implemented to create a more positive school environment. This paper offers a description of these prevention programs, focussing on the three most commonly implemented in schools: TEI, KiVa and Mediation Teams. A qualitative, descriptive and comparative analysis was made using semi-structured interviews with tutors, coordinators and experts at nine schools, three schools fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…[10] , which also concluded that individuals are well-informed about different forms of bullying and their legal repercussions. [11] research, suggesting that participation in bullying prevention programs increases satisfaction among those aware of them.…”
Section: Resultsmentioning
confidence: 99%
“…[10] , which also concluded that individuals are well-informed about different forms of bullying and their legal repercussions. [11] research, suggesting that participation in bullying prevention programs increases satisfaction among those aware of them.…”
Section: Resultsmentioning
confidence: 99%
“…terhadap perilaku yang tidak dapat diterima, (c) Secara konsisten menghindari hukuman yang menyebabkan konsekuensi negatif dan destruktif jika terjadi pelanggaran aturan, dan bertindak sebagai model yang dapat ditiru . (Sainz & Martín-Moya, 2023) (Saraswati & Hadiyono, 2020) Dalam beberapa kasus, peran sekolah dalam mencegah bullying masih minim. Banyak sekolah tampaknya menutupi masalah bullying dan menganggapnya sebagai sesuatu yang benar.…”
Section: Menggambarkan Budaya Stop Bullyingunclassified
“…There are numerous prevention and intervention programs and projects against this type of violence, focused on different areas which are implemented in schools [26,27]. However, there is limited scientific evidence regarding the validity of these school bullying prevention programs [28,29], posing new challenges and opportunities in the development of these programs [30].…”
Section: The Tei Program For the Prevention Of School Bullyingmentioning
confidence: 99%